Contributions to the Analysis of Amendments of the Crime Ctipulated in Article 43 of Law no. 255/1998 on the Protection of New Varieties of Plants Made by Law no. 187/2012 for the Enforcement of Law no. 286/2009 on the Criminal Code - Florea, Bujorel (Journal of Economic Development, Environment and People, 2016)
The article brings into question the criminal protection of new varieties of plants. The author presents certain judicial norms, as previous issues, concerning the occurrence and protection of the rights over new varieties of plants through the granting of the variety patent. Furthermore, the study indicates the amendments made by Law no. 187/2012 on the enforcement of Law no. 286/2009 on the Criminal Code, concerning the counterfeiting crime incriminated in Law no. 255/1998 on the protection of new varieties of plants. Finally, the author underlines the specific elements of the contents of the investigated crime, thus providing the concerned parties with a table enabling, through the implementation thereof, the detection of the determining factors in the establishment and holding of the criminal liability of individuals infringing the rights of the plant variety patent holders, through counterfeiting.